The Acquisitions Budget, 1st edition - Katz, Bill (Routledge, 2020)
This book, first published in 1989, discusses the maintenance of a quality collection within a budget while still making necessary cuts and savings. As the purchasing power of the materials budget declines, effectively managing the allocation of the materials budget and the development of the collections becomes more and more of a challenge. In The Acquisitions Budget, practicing acquisitions librarians - representing almost all types and sizes of libraries - address their daily problems and share innovative and effective methods for dealing with a shrinking budget. These authoritative contributors, who have many years of practical problems solving experience, also offer useful tips on how to influence administrators, faculty, students - anyone who has even partial control over allocating the budget.